Strength and force distribution of lap-welded composite longitudinal reinforcing bars formed during strengthening of reinforced concrete beam elements by increasing the cross-section in the tension zone - Azizova, Anna; Ovsii, Dmytro; Semko, Oleksandr; Ovsii, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article experimentally investigated the strength and stress-strain state of eccentrically stretched specimens from welded overlapped longitudinal reinforcing bars, which have cross-sections varying in length and are interconnected by electric arc welding. The strength of reinforcing bars of a composite cross-section was compared with the strength of individual centrally stretched reinforcing bars. As a result of the experiment, the influence of the main factors on the strength of the bars was investigated: electric arc welding; stress concentration; eccentricity of the application of longitudinal tensile force, as well as the distribution of forces in the sections of each element along the length of the composite reinforcing bar-sample